2015
DOI: 10.1111/bjop.12116
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural evidence of value structures and priorities in childhood

Abstract: We broaden the developmental focus of the theory of universals in basic human values (Schwartz, 1992, Advances in Experimental Social Psychology) by presenting supportive evidence on children's values from six countries: Germany, Italy, Poland, Bulgaria, the United States, and New Zealand. 3,088 7-11-year-old children completed the Picture-Based Value Survey for Children (PBVS-C, Döring et al., 2010, J. Pers. Assess., 92, 439). Grade 5 children also completed the Portrait Values Questionnaire (PVQ, Schwartz, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
80
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 58 publications
12
80
0
3
Order By: Relevance
“…This underscores parents' role as socializing agents who transmit values that prevail in the wider context of society. Family members' gender also played an important role: Males' and females' value priorities differed (see D€ oring et al, 2015, 2016Schwartz & Rubel, 2005). Additionally, mothers' values were more similar to their children's values than fathers' values in the Swiss sample (Study 1), and daughters' values were more similar to their parents' values than sons' values in the German sample (Study 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This underscores parents' role as socializing agents who transmit values that prevail in the wider context of society. Family members' gender also played an important role: Males' and females' value priorities differed (see D€ oring et al, 2015, 2016Schwartz & Rubel, 2005). Additionally, mothers' values were more similar to their children's values than fathers' values in the Swiss sample (Study 1), and daughters' values were more similar to their parents' values than sons' values in the German sample (Study 2).…”
Section: Discussionmentioning
confidence: 99%
“…Across a range of studies, the PBVS-C showed to have good structural validity, as structural analyses yielded a clear distinction between the four higher-order values (Cieciuch, Davidov, & Algesheimer, 2016;Cieciuch, D€ oring, & Harasimczuk, 2013;D€ oring et al, 2010, 2015Uzefovsky et al, 2016). Multitrait-multimethod analyses of data from older children who were capable of completing an established values questionnaire for adults (the Portrait Values Questionnaire, PVQ, see below) in addition to the PBVS-C confirmed concurrent validity (Cieciuch et al, 2013;D€ oring et al, 2015): Correlations for the higher-order values measured across both instruments ranged from .42 to .72. The higher-order values as measured with the PBVS-C were further shown to be relatively stable over time: For 8-to 11-year-old children, Cieciuch et al (2016) report a stability of between .25 and .63 over 1 year and between .14 and .43 over 2 years.…”
Section: Study 1 Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent benevolence and universalism (self-transcendence) are highly related at one pole and power and achievement are highly related at the opposing pole (self-enhancement) and these findings hold across samples from multiple countries (Döring et al, 2015).…”
supporting
confidence: 64%
“…Like adults, children tend to rate self-transcendence values as most important and selfenhancement values as least important (Döring et al, 2015). Value priorities for 8-to 11-yearolds are moderately stable over two year periods (Cieciuch, Davidov, & Algesheimer, 2016).…”
mentioning
confidence: 99%